2019
DOI: 10.1002/ajhb.23331
|View full text |Cite
|
Sign up to set email alerts
|

Association between second to fourth digit ratio and personality among Indian men

Abstract: Objectives To examine the relationship between the personality domains with the second to fourth digit ratio (2d:4d); a prenatal testosterone exposure marker. Methods The 2d:4d for both hands was measured for the Indian male subjects' (n = 994). Ten‐item personality inventory and displaced aggression questionnaire data were collected in a self‐reported proforma in this cross sectional study with a convenient sampling approach. Results The personality traits, namely openness to new experiences, carelessness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…Therefore, our results indicate that lower 2D:4D is associated with lower emotional stability (higher neuroticism) in women, and consequently we presume that is also associated with higher prenatal testosterone exposure. These results are partially in disagreement with previous studies which found a relationship between 2D:4D and the neuroticism-emotional stability dimension but seem to be in the PLOS ONE opposite direction [28,29,35,[39][40][41][42]; or, conversely, have found no relationship between these variables [30][31][32][33][36][37][38]. In most of the previous studies neuroticism was measured through the Neo Five-Factor Inventory, and here we measured emotional stability through the BFQ.…”
Section: D:4d Is Positively Related To Emotional Stability But Not Wcontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, our results indicate that lower 2D:4D is associated with lower emotional stability (higher neuroticism) in women, and consequently we presume that is also associated with higher prenatal testosterone exposure. These results are partially in disagreement with previous studies which found a relationship between 2D:4D and the neuroticism-emotional stability dimension but seem to be in the PLOS ONE opposite direction [28,29,35,[39][40][41][42]; or, conversely, have found no relationship between these variables [30][31][32][33][36][37][38]. In most of the previous studies neuroticism was measured through the Neo Five-Factor Inventory, and here we measured emotional stability through the BFQ.…”
Section: D:4d Is Positively Related To Emotional Stability But Not Wcontrasting
confidence: 99%
“…Two Italian investigations with the Big Five Questionnaire (BFQ) found a positive relationship with conscientiousness and agreeableness in a sample of skydivers [36], and a positive relationship with conscientiousness in a sample of cavers [37]. Recently, using the ten-item personality inventory a positive relationship have been found between the right 2D:4D and openness to new experiences and a negative one with disorganization and carelessness [38]. Additionally, in the same study they found a negative relationship between the left 2D:4D and dependable self-disciplined.…”
Section: Introductionmentioning
confidence: 99%
“…At the population level, males exhibit lower 2D:4D values compared with females (Zheng & Cohn, 2011). Lower 2D:4D values has been shown to be associated with several behavioral and personality traits (Bagepally et al, 2020), including religiosity (Richards et al, 2018).…”
Section: Introductionmentioning
confidence: 99%